Identification of the potential dual inhibitor of protein tyrosine phosphatase sigma and leukocyte common antigen-related phosphatase by virtual screen, molecular dynamic simulations and post-analysis. Issue 1 (2nd January 2021) - Zhou, Liang; Ma, Yang-Chun; Tang, Xue; Li, Wei-Ya; Ma, Ying; Wang, Run-Ling
Abstract: Owing to their inhibitory role in regulating oligodendrocyte differentiation and apoptosis, protein tyrosine phosphatase sigma (PTPσ) and leukocyte common antigen-related phosphatase (LAR) play a crucial potential role in treating spinal cord injury (SCI) disease. In this research, the computer aided drug design (CADD) methods were applied to discover the potential dual-target drug involving virtual screen, molecular docking and molecular dynamic simulation. Initially, the top 20 compounds with higher docking score than the positive controls (ZINC13749892, ZINC14516161) were virtually screened out from NCI and ZINC databases, and then were submitted in ADMET to predict their drug properties. Among these potential compounds, ZINC72417086 showed a higher docking score and satisfied Lipinski's rule of five. In addition, the post-analysis demonstrated that when ZINC72417086 bound to PTPσ and LAR, it could stable proteins conformations and destroy the residues interactions between P-loop and other loop regions in active pocket. Meanwhile, residue ARG1595 and ARG1528 could play a crucial role in in the inhibition of PTPσ and LAR, respectively. This research offered a novel approach for rapid discovery of dual-target leads compounds to treat SCI. Communicated by Ramaswamy H. Sarma